Acquisition of artifact free alkali metal distributions in SiO2 by ToF‐SIMS Cs+ depth profiling at low temperatures. (13th May 2021) - Leitzenberger, Michael; Kuegler, Peter; Krivec, Stefan; Hutter, Herbert
Abstract : Artifact‐free depth profiles of alkali ions in SiO2 were obtained using a time‐of‐flight secondary ion mass spectrometer (ToF‐SIMS) equipped with a Cs + beam as sputter gun. Samples were set to low temperature ( −100°C) using a heating/cooling sample holder. The effects of temperature on the depth profiles was determined with multiple measurements at different temperatures. To validate the described method, obtained depth profiles of alkali metal implanted SiO2 samples were compared with simulated depth profiles. Evidence for artifact‐free depth profiles is given for potassium, sodium, and lithium, three prominent examples of fast diffusing ions in various materials. This described approach enables more laboratories to acquire depth profiles of alkali metals in non‐conducting samples without time‐consuming sample preparation. It offers artifact‐free depth profiling of alkali metals using a classic ToF‐SIMS without advanced extensions, which are not available in many laboratories.